Significant decline of a Common Buzzard Buteo buteo population during an outbreak of high pathogenicity avian influenza (HPAI) - Swann, Robert L.; Beckmann, Björn C. (Bird study, 2025)
In a study population of Common Buzzards Buteo buteo in Easter Ross in eastern Highland, Scotland, numbers remained largely stable between 1996 and 2021, averaging 54 occupied territories. There was weak evidence for a gradual long-term decline by one pair every five to six years over this period. In 2020 and 2021, 58 occupied territories were confirmed, but this fell to 42 and 44 occupied territories respectively in 2022 and 2023, a fall much greater than the population variability observed over the previous 26 years. The decline coincided with an unprecedented outbreak of high pathogenicity avian influenza (HPAI) in populations of other species, including Pink-footed Geese Anser brachyrhynchus, many of which died in the study area in spring 2022. Two dead Common Buzzards and 15 dead geese recovered in and around the study area between December 2021 and May 2022 tested positive for HPAI. No Common Buzzards were directly observed feeding on dead geese, but the study provides strong circumstantial evidence for a significant, population-level impact of HPAI on this scavenging raptor, with no evidence for other sudden environmental changes in the study area to explain such a population decline. Corroborating observations included a reduction in the mean number of chicks fledged per occupied territory in 2022, despite above-average clutch sizes, which would be consistent with breeding birds continuing to be affected by HPAI post-laying.